Pengaruh Efektivitas, Kepercayaan, Dan Kemudahan Terhadap Minat Penggunaan QRIS Di Kota Malang - Berliana, Alvi Sinta; Farida, Eka; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of effectiveness, trust, and ease of use on the intention to use QRIS (Quick Response Code Indonesian Standard) in Malang City. QRIS is a digital payment innovation authorized by Bank Indonesia to facilitate non-cash transactions in a more efficient and secure manner. The research applied a quantitative approach using an explanatory research design. The sample consisted of 100 respondents selected through purposive sampling. Data were analyzed using multiple linear regression analysis. The results indicate that effectiveness, trust, and ease of use simultaneously have a significant influence on the intention to use QRIS. Partially, all three variables also have a positive and significant influence. These findings support the Technology Acceptance Model (TAM), which explains that users’ perceptions of ease of use, system reliability, and usefulness play an essential role in technology adoption. Therefore, increasing public interest in using QRIS can be achieved by ensuring the system is effective, trustworthy, and easy to use Keywords: QRIS, Effectiveness, Trust, Ease Of Use, Usage Intention